PENGARUH KEMAMPUAN PENALARAN DAN KEMAMPUAN BERPIKIR REFLEKTIF TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS DITINJAU DARI SELF CONFIDENCE - Syafitri Rahma Suci, Ifada; Sri Anggoro, Bambang; Ulfa Nabila, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the direct and indirect influence between reasoning skills and reflective thinking skills on mathematical critical thinking skills through students' self-confidence. This study uses a quantitative approach with correlational methods and path analysis. The research population is grade VIII students of State Junior High School in Sukarame District with a sample of 288 students selected using stratified random sampling techniques. The research instruments include reasoning ability tests, reflective thinking ability tests, mathematical critical thinking ability tests, and self-confidence questionnaires that have met valid and reliable criteria. The results showed that reasoning skills and reflective thinking skills had a positive and significant effect on self confidence by 0.247 and 0.186, respectively. In addition, reasoning skills, reflective thinking skills, and self-confidence have a positive and significant effect on mathematical critical thinking skills with a path coefficient of 0.183 each; 0,188; and 0.224. The results of the mediation test showed that self confidence did not significantly mediate the influence of reasoning ability and reflective thinking ability on mathematical critical thinking ability. Simultaneously, the three variables contributed 43.0% to the ability to think critically mathematically.